Descriptions of the larva and pupa of Mecynodera balyi Clark, 1864, with notes on its life history (Coleoptera: Chrysomelidae: Sagrinae) - Reid, Chris A.m.; Beatson, Max (Zootaxa, 2019)
The larva and pupa of the sagrine chrysomelid Mecynodera balyi Clark, 1864 are described and life history notes provided for this species. The larva of Mecynodera balyi is spermophagous and feeds inside seed pods of Pandorea, a vine in the Bignoniaceae. This is the first record of larval spermophagy in any chrysomelid other than Bruchinae, the sister subfamily to Sagrinae. Several morphological features of the immature stages are newly recorded for the Sagrinae. The implications of these new data for systematic placement of Sagrinae are discussed.